Dispersion Modeling of Sulfur and Nitrogen Oxides Emissions from Stationary Sources in Banias –Syria - شيبان سامية; سلمان هناء (Latakia University Journal -Engineering Sciences Series, 2021)
Power plants and oil refineries are important sources of sulfur dioxide and nitrogen oxides emissions, which spread to large distances away from their original sources. Air pollution modeling is widely used to predict concentrations of pollutants in relation to various operating and metrological conditions. This study aims to predict the emissions of sulfur dioxide (SO2) and nitrogen oxides (NOx) from two adjacent point sources in Banias; the power plant and oil refinery company, using MATLAB for analytical solution of 3D advection-dispersion Gaussian equation, and to identify the most affected areas according to the most dominated metrological conditions. Four scenarios were investigated taking into account variations in pollutants concentration with regard to wind speed and its direction. The results showed that the main risk was due to Sulphur dioxide emissions, where its concentrations exceeded the guideline limits (50 µg/m3 annual average) for most periods of the year in an area of less than 10 square kilometers surrounding the power station and the oil refinery, the concentrations were 100 µg/m3 at 5 km from the its sources. The worst condition has been found to be when the wind direction is south-west, resulting in large area being exposed to the combined impact of the emission of pollutants from both facilities.